A comparative study of help-seeking behavior in an urban community. - Cruz, Erlinda B.
People have varied ways of medical help-seeking. Some subscribe only to medical health workers while others utilize both the indigenous and professional health practitioners. The same clients may secure preventive care and early treatment of illness conditions or practice informal consultations and seek treatment only when the illness has become severe. Several factors account for these variables in medical help-seeking.
The review of literature revealed a wide range of possible factors that can influence medical help-seeking from socio-economic and demographic characteristics of clients as well as patient-professional relationships to illness severity and accessibility of health resources.
Cognizant of the numerous factors that affect help-seeking behavior, this study limited its focus to the clients' socio-economic and psychological characteristics. It is hypothesized that clients possessing most if not all of the enabling characteristics are likely to utilize only the medical health workers and practice preventive care as well as early treatment of illness conditions. The opposite is predicted for clients possessing most of the inhibiting characteristics.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Health attitudes -- Philippines -- San Francisco del Monte, Quezon City; Medical care -- Philippines -- San Francisco del Monte, Quezon City